Translators’ Changing Habitus: A Source Orientation in Subtitling Chinese Fifth-Generation Directors’ Films? - Sun, Xichen (Journal of Audiovisual Translation, 2025)
This paper examines the evolving habitus of English translators/subtitlers working on films (1984–2024) by Chinese fifth-generation directors Chen Kaige and Zhang Yimou. An analysis of 32 films shows a significant shift: initially dominated by native English speakers from the cultural industries or the Chinese studies circle, currently, the field of Chinese film translation has attracted native Chinese speakers with film industry or audiovisual translation (AVT) experience. The decreased reliance on foreign language experts and a corresponding increase in the selection of source-situated translators/subtitlers indicate a divergence from the norm of translating into one’s first language. The reasons behind this divergence lie in the influence of the marketisation of China’s film industry, the filmmakers’ increasing focus on the domestic market—especially after the pandemic—and the professionalisation of AVT in China. Employing Bourdieu’s theory, this study analyses the translators’/subtitlers’ educational backgrounds and career trajectories, focusing on their experience with the Chinese language and China. It identifies three phases in the evolution of their habitus: target-culture translators/subtitlers in the early centralised era, industry-experienced translators/subtitlers after the film marketisation, and domestic translators/subtitlers since the pandemic. Lay summary Zhang Yimou and Chen Kaige are two of the most prominent filmmakers in the contemporary Chinese film industry, widely recognised as leading figures among the Chinese fifth-generation directors, also known as Chinese New Wave auteurs. Their groundbreaking collaboration on The Yellow Earth (1984), created shortly after their graduation from the Beijing Film Academy, marked a turning point that brought Chinese cinema onto the international stage. Since then, both directors have achieved global renown, producing numerous influential works. To explore how their films have been made accessible to English-speaking audiences, I examined the end credits of 17 films by Chen and 25 by Zhang, focusing on those credited with English subtitling, often labelled as “English Subtitles,” “English Translation,” “English Subtitle Translation,” “Translation,” or “Translator” etc. Through this process, I discovered 46 individuals involved in translating or subtitling these works, of whom 19 were identified for further analysis based on online profile searches. I then researched the linguistic skills, educational backgrounds, and professional experiences of these 19 translators or subtitlers to understand their development trajectories through the lens of Bourdieu’s concept of habitus. A translator’s habitus is the disposition guiding their decisions, shaped by childhood, education, and the pursuit of capital within the field. This analysis revealed a shift in subtitling practices—from relying primarily on native English speakers from the culture industry or Chinese studies circle to recruiting native Chinese speakers with Chinese film industry experience or translation expertise—a change that reflects a broader trend in Chinese film subtitling. This evolution challenges the conventional norm of translating exclusively into one’s native language. In examining this norm’s breach, I considered several factors: the increasing marketisation of the Chinese film industry, the recent emphasis on the domestic film market, the growth of Chinese film and television translation companies, and the establishment of industry-specific translation associations. Lay summary Zhang Yimou and Chen Kaige are two of the most prominent filmmakers in the contemporary Chinese film industry, widely recognised as leading figures among the Chinese fifth-generation directors, also known as Chinese New Wave auteurs. Their groundbreaking collaboration on The Yellow Earth (1984)—with Chen serving as director and Zhang as cinematographer—shortly after their graduation from the Beijing Film Academy, marked a turning point that brought Chinese cinema onto the international stage. Since then, both directors have achieved global renown, producing numerous influential works. To explore how their films have been made accessible to English-speaking audiences, I examined the end credits of 17 films by Chen and 25 by Zhang, focusing on those credited with English subtitling, often labelled as “English Subtitles,” “English Translation,” “English Subtitle Translation,” “Translation,” or “Translator” etc. Through this process, I discovered 46 individuals involved in translating or subtitling these works, of whom 19 were identified for further analysis based on online profile searches. I then researched the linguistic skills, educational backgrounds, and professional experiences of these 19 translators or subtitlers to understand their development trajectories through the lens of Bourdieu’s concept of habitus. A translator’s habitus is the disposition guiding their decisions, shaped by childhood, education, and the pursuit of capital within the field. This analysis revealed a shift in subtitling practices—from relying primarily on native English speakers from the culture industry or Chinese studies circle to recruiting native Chinese speakers with Chinese film industry experience or translation expertise—a change that reflects a broader trend in Chinese film subtitling. This evolution challenges the conventional norm of translating exclusively into one’s native language. In examining this norm’s breach, I considered several factors: the increasing marketisation of the Chinese film industry, the recent emphasis on the domestic film market, the growth of Chinese film and television translation companies, and the establishment of industry-specific translation associations.